Effect of apical chloride concentration on the measurement of responses to CFTR modulation in airway epithelia cultured from nasal brushings - Bratcher, Preston E. (Physiol Rep, 2020)
INTRODUCTION: One method for assessing the in vitro response to CFTR‐modulating compounds is by analysis of epithelial monolayers in an Ussing chamber, where the apical and basolateral surfaces are isolated and the potential difference, short‐circuit current, and transepithelial resistance can be monitored. The effect of a chloride ion gradient across airway epithelia on transepithelial chloride transport and the magnitude of CFTR modulator efficacy were examined. METHODS: CFTR‐mediated changes in the potential difference and transepithelial currents of primary human nasal epithelial cell cultures were quantified in Ussing chambers with either symmetrical solutions or reduced chloride solutions in the apical chamber. CFTR activity in homozygous F508del CFTR epithelia was rescued by treatment with VX‐661, C4/C18, 4‐phenylbutyrate (4‐PBA) for 24 hr at 37°C or by incubation at 29°C for 48 hr. RESULTS: Imposing a chloride gradient increased CFTR‐mediated and CaCC‐mediated ion transport. Treatment of F508del CFTR homozygous cells with CFTR modulating compounds increased CFTR activity, which was significantly more evident in the presence of a chloride gradient. This observation was recapitulated with temperature‐mediated F508del CFTR correction. CONCLUSIONS: Imposing a chloride gradient during Ussing chamber measurements resulted in increased CFTR‐mediated ion transport in expanded non‐CF and F508del CFTR homozygous epithelia. In F508del CFTR homozygous epithelia, the magnitude of response to CFTR modulating compounds or low temperature was greater when assayed with a chloride gradient compared to symmetrical chloride, resulting in an apparent increase in measured efficacy. Future work may direct which methodologies utilized to quantify CFTR modulator response in vitro are most appropriate for the estimation of in vivo efficacy.